2021
DOI: 10.3389/fonc.2021.695001
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Verification and Pathway Enrichment Analysis of Prognosis-Related Immune Genes in Patients With Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma is a common malignant tumor with poor prognosis, poor treatment effect, and lack of effective biomarkers. In this study, bioinformatics analysis of immune-related genes of hepatocellular carcinoma was used to construct a multi-gene combined marker that can predict the prognosis of patients. The RNA expression data of hepatocellular carcinoma were downloaded from The Cancer Genome Atlas (TCGA) database, and immune-related genes were obtained from the IMMPORT database. Differential analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…In HCC, NR6A1 was identified as a prognostic marker, and associated with sorafenib resistance in HCC patients 27 . Lin et al showed that NR6A1 might inhibit the HCC immune response 28 and activate the WNT signaling pathway as well as MTOR-signaling pathway 29 , which were similar to our study. On the other hand, NR6A1 could enhance HCC proliferation and invasion in vitro and vivo 29 , which indicated that NR6A1 showed promise as a novel immune therapeutic target for HCC.…”
Section: Discussionsupporting
confidence: 92%
“…In HCC, NR6A1 was identified as a prognostic marker, and associated with sorafenib resistance in HCC patients 27 . Lin et al showed that NR6A1 might inhibit the HCC immune response 28 and activate the WNT signaling pathway as well as MTOR-signaling pathway 29 , which were similar to our study. On the other hand, NR6A1 could enhance HCC proliferation and invasion in vitro and vivo 29 , which indicated that NR6A1 showed promise as a novel immune therapeutic target for HCC.…”
Section: Discussionsupporting
confidence: 92%
“… 22 Recently, a five-gene ( HDAC1, BIRC5, SPP1, STC2, and NR6A1 ) prognostic model was established for the prediction of overall survival in patients with HCC. 23 However, the performance of the model was only of acceptable predictive ability, and there was no in vitro or in vivo validation. 23 Moreover, the expression profile and molecular biological functions of NR6A1 during the development and progression of HCC, and its prognostic significance remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“… 23 However, the performance of the model was only of acceptable predictive ability, and there was no in vitro or in vivo validation. 23 Moreover, the expression profile and molecular biological functions of NR6A1 during the development and progression of HCC, and its prognostic significance remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The FBXO17 and PPARGC1A genes were identified as gene signatures for colon cancer and could be useful in predicting the survival outcome and establishing the appropriate treatment strategy [ 20 ]. The HDAC1, BIRC5, SPP1, STC2, and NR6A1 genes have been proposed as prognostic models of immune genes in hepatocellular carcinoma [ 21 ]. The nine glycolysis-related genes were identified as predictive signatures and may function as independent and important risk factors for ovarian cancer [ 22 ].…”
Section: Introductionmentioning
confidence: 99%